2017
DOI: 10.18632/oncotarget.22754
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of genome-wide age-related DNA methylation in breast tissue

Abstract: Despite known age-related DNA methylation (aDNAm) changes in breast tumors, little is known about aDNAm in normal breast tissues. Breast tissues from a cross-sectional study of 121 cancer-free women, were assayed for genome-wide DNA methylation. mRNA expression was assayed by microarray technology. Analysis of covariance was used to identify aDNAm’s. Altered methylation was correlated with expression of the corresponding gene and with DNA methyltransferase protein DNMT3A, assayed by immunohistochemistry. Publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 54 publications
4
52
0
Order By: Relevance
“…In this study, we identified age-related methylation sites that were consistently reported in normal breast tissue across at least two previously published studies [4,6,7]. We confirm that previously reported age-related methylation in normal breast tissue is also present to a large degree in tumouradjacent normal tissue and among Asian women.…”
Section: Introductionsupporting
confidence: 89%
“…In this study, we identified age-related methylation sites that were consistently reported in normal breast tissue across at least two previously published studies [4,6,7]. We confirm that previously reported age-related methylation in normal breast tissue is also present to a large degree in tumouradjacent normal tissue and among Asian women.…”
Section: Introductionsupporting
confidence: 89%
“…We obtained Illumina 450k DNAm data from studies profiling normal tissue, not adjacent to cancer. Briefly, we obtained normal samples from the lung (n = 21) [36], breast (n = 171: 50 derived from [37] and 121 from [61]), oral/buccal (n = 790) [36], liver (n = 26) [62], stomach (n = 61) [24], colon (n = 8) [63], skin (n = 19) [64], esophagus (n = 52) [28], and whole blood (n = 487: 335 from Liu et al [65] and 152 from Teschendorff et al [36]). In all cases, we used the normalized data as described in our previous publications, or were normalized de novo using the same procedure as in these previous studies, i.e., using minfi [66] and BMIQ [67].…”
Section: Normal (Non-adjacent) Tissue Dnam Datasetsmentioning
confidence: 99%
“…The main Illumina DNA methylation 450k datasets used here are freely available from public repositories, including GEO (www.ncbi.nlm.nih.gov/geo), ArrayExpress (www.ebi.ac.uk/arrayexpress), and EGA (www.ebi.ac.uk/ega/home) (see Methods for relevant references). Details: Hannum (656 whole blood, GEO: GSE40279) [47]; MESA (214 purified CD4+ T cells and 1202 Monocyte samples, GEO: GSE56046 and GSE56581) [69]; Tserel (98 CD8+ T cells, GEO: GSE59065) [70]; BLUEPRINT (139 matched CD4+ T cells, Monocytes and Neutrophils, EGA: EGAS00001001456) [72]; Liu (335 whole blood, GEO: GSE42861) [65]; Gastric tissue (191 normal and metaplasia, GEO: GSE103186) [24]; Colon tissue (47 normal and adenoma, ArrayExpress: E-MTAB-6450) [63]; Breast Erlangen (50 normal, GEO: GSE69914) [37]; Breast2 (121 normal, GEO: GSE101961) [61]; Liver (26 normal, GEO: GSE61258) [62]; Skin (19 epidermal non-sun exposed, GEO: GSE51954) [64]; Esophagus (52 normal, GEO: GSE104707) [28]; SCM2 (37 fetal tissue samples, GEO: GSE31848) [45]; Cord blood (15 samples, GEO: GSE72867) [46]. TCGA data was downloaded from https://gdc.cancer.gov.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…A total of 319,607 probes (No Pruned Set) passed our quality control and 128,405 probes (Pruned Set) were retained after pruning based upon the pairwise correlation of probes (see next section). To test the performance of age predictors in non-blood tissues, we downloaded 13 cohorts from GEO database with accession ID GSE61431 (brain) 37 , GSE59685 (brain) 38 GSE80970 (brain), GSE101961 (breast) 39 , GSE108213 (breast), GSE48325 (liver) 40 , GSE61257 (adipose) 41 , GSE61258 (liver) 41 , GSE61259 (breast) 41 , GSE88883 (breast) 42 , GSE90060 (endometrium) 43 , GSE92767 (saliva) 44 , GSE99029 (saliva) 45…”
Section: Methodsmentioning
confidence: 99%